4(7x + 10) = 3(9x – 5) + 20
28x + 40 = 27x - 15 + 20
28x + 40 = 27x + 5
x = -35
2007-01-27 11:05:33
·
answer #1
·
answered by Anonymous
·
1⤊
0⤋
4(7x + 10) = 3(9x - 5) + 20 Mulitply out to get rid of ( )
28x + 40 = 27x - 15 + 20 Subtract 27x from both sides
x + 40 = 5 Subtract 40 from both sides
x=-35
2007-01-27 19:16:14
·
answer #2
·
answered by Michelle M 2
·
1⤊
0⤋
4(7x + 10)= 3(9x -5) + 20
28x + 40 = 27x - 15 + 20
28x - 27x = -15 + 20 - 40
x = -35
2007-01-27 19:17:26
·
answer #3
·
answered by cute_gurl 1
·
1⤊
0⤋
4(7x + 10) = 3(9x – 5) + 20
28x + 40 = 27x - 15 + 20
28x + 40 = 27x + 5
x = -35
So you multiply though and then solve for x.
2007-01-27 19:09:40
·
answer #4
·
answered by abe_cooldude 1
·
1⤊
0⤋
First: eliminate parenthesis - use distribution > multiply the outer term with the terms in parenthesis...
4(7x) + 4(10) = 3(9x) + 3(-5) + 20
28x + 40 = 27x - 15 + 20
28x + 40 = 27x + 5
Sec: combine "like" terms > subtract "40" from both sides...
28x + 40 - 40 = 27x + 5 - 40
28x = 27x - 35
*Subtract "27x" from both sides...
28x - 27x = 27x - 27x - 35
x = - 35
2007-01-27 19:11:35
·
answer #5
·
answered by ♪♥Annie♥♪ 6
·
1⤊
0⤋
28x + 40 = 27x - 15 + 20
28x - 27x = -15 + 20 - 40
x = -35
2007-01-27 19:11:39
·
answer #6
·
answered by Brian 3
·
1⤊
0⤋
x = - 35
28x + 40 = 27x -15 + 20
28x + 40 = 27x + 5
You need to get your x's on one side and vise versa.
28x-27x = x & -45 +5 = -35 , so
x = -35
I hope this helps!
2007-01-27 19:11:27
·
answer #7
·
answered by Trish 2
·
1⤊
0⤋
28x+40=27x-15+20
x=-35
2007-01-27 20:03:32
·
answer #8
·
answered by quasar 1
·
1⤊
0⤋
-35
2007-01-27 19:06:21
·
answer #9
·
answered by cosmin 1
·
2⤊
2⤋